2018
DOI: 10.1590/1679-78254119
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of truss systems with stiffened flattened end-bars

Abstract: Circular hollow sections are usually used in long-span roof truss systems. One of the typology for connecting elements in such structures involves the flattening of bar ends. This article presents the numerical analysis of a plane truss composed of circular hollow sections, in which diagonal bars have flattened ends. In this sense, a new flattening typology called stiffened flattening is proposed, characterized by a non-flat geometry, with the creation of stiffeners in the lateral edges of the diagonal flatten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The Brazilian standard of circular hollow sections ABNT NBR 16239:2013 [26] presents prescriptions for the determination of the axial compression strength of calculation for prismatic bars. It is emphasized that the standard provides resistance capacity without regarding the bars flattened-ends and eccentricities [30]. ABNT NBR 16239:2013 [26] considers that the sizing of bars under compression load must be carried out in accordance with the requirements of ABNT NBR 8800:2008 [31].…”
Section: Analytical Strength Of Bars Under Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brazilian standard of circular hollow sections ABNT NBR 16239:2013 [26] presents prescriptions for the determination of the axial compression strength of calculation for prismatic bars. It is emphasized that the standard provides resistance capacity without regarding the bars flattened-ends and eccentricities [30]. ABNT NBR 16239:2013 [26] considers that the sizing of bars under compression load must be carried out in accordance with the requirements of ABNT NBR 8800:2008 [31].…”
Section: Analytical Strength Of Bars Under Compressionmentioning
confidence: 99%
“…ABNT NBR 16239:2013 [26] considers that the sizing of bars under compression load must be carried out in accordance with the requirements of ABNT NBR 8800:2008 [31]. However, it presents its own curve to calculate the reduction factor associated with the axial compression load for tubular profiles [30]. Thus, the computation of the axial compression strength of calculation given by:…”
Section: Analytical Strength Of Bars Under Compressionmentioning
confidence: 99%
“…Zhou et al investigated the response of an 8-story steel staggered-truss system, utilizing a scaled model at 1/8th size subjected to reversed low cyclic loading, and put forward some suggestions for the design of a staggered-truss structure 2 . Amélia et al created a new flattening typology by incorporating stiffeners in the lateral edges of the diagonal flattened ends, and found that this stiffened flattening technique can simplify the structural design of the plane and multi‐planar trusses 3 . To replace traditional reinforcement methods for coupling beams used within shear wall system, Chairunnisa et al modeled a simplified version of a coupling beam using steel truss configurations made from steel angle profiles and found that this kind of steel truss-coupling beam can show fairly well behavior under lateral load 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There are high concentrations of stress on the nodal region, separation and slip between bars, which can sensibly increase the loss of bearing capacity with the emergence of bending moment [4,11,16]. (c) The eccentricities in the connections can cause increases of stress for a reduced nodal stiffness [17,18]. Another characteristic worth emphasizing refers to the collapse of special trusses with typical joints, which occurs because of the collapse of the connection with inefficient use of the bar's strength capability [19].…”
Section: Introductionmentioning
confidence: 99%